ANALISA DAMPAK REVALUASI ASET TETAP BERDASARKAN PERATURAN MENTERI KEUANGAN NO.191/PMK.010/2015 TAHUN 2015 DALAM PERHITUNGAN BEBAN PAJAK PENGHASILAN (Studi Kasus Pada Pt. XYZ di Mojokerto) - Syukroni, Muhammad Amar; Hwihanus, Hwihanus (JEA17: Jurnal Ekonomi Akuntansi, 2017)
ABSTRACTThis research discusses the implementation of revaluation of fixed assets by taking a case study at PT. XYZ in 2015. PT. XYZ is a company engaged in industrial services for a variety of special works of metals and metal goods. PT. XYZ conducts revaluation of fixed assets for taxation purposes. Tax regulations which are the basis for the revaluation of fixed assets at PT. XYZ is PMK 191 / PMK.010 / 2015, PMK 233 / PMK.03 / 2015, and PMK 29 / PMK.03 / 2016. The research method used is descriptive qualitative with the aim to determine the application of PMK 191 / PMK.010 / 2015 to the implementation of revaluation of fixed assets at PT. XYZ and the impact on the financial statements. The results of this study are the revaluation of fixed assets by PT. XYZ is in accordance with applicable tax regulations. Impact arising on the financial statements of PT. XYZ is an increase in the balance of fixed assets, equity, tax debt, and a decrease in the ratio of debt to equity. Tax implications that arise are PT. XYZ must pay taxes on revaluation of Rp 251,006,279. Depreciation expenses which increase due to increasing value of fixed assets are a deduction from operating income in the calculation of corporate tax expenses. However, it should also be considered that revaluation creates new costs, including appraisal services fees and Final Income Tax debt. Keywords: revaluation of fixed assets, taxes, PMK 191 / PMK.010 / 2015, financial statements